Stress-related factors in the emergence of transient global amnesia with hippocampal lesions - Döhring, Juliane; Schmuck, Alexander; Bartsch, Thorsten (Frontiers in Behavioral Neuroscience, 2014)
The transient global amnesia (TGA) is a rare amnesic syndrome that is characterized by an acute onset episode of an anterograde and retrograde amnesia. Its origin is still debated, but there is evidence for psychological factors involved in TGA. In neuroimaging, selective lesions in the CA1 fields of the hippocampus can be detected, a region that is particularly involved in the processing of memory, stress and emotion. The aim of this study was to assess the role of psychological stress in TGA by studying the prevalence of stress related precipitating events and individual stress-related personality profiles as well as coping strategies in patients. The hypothesis of a functional differentiation of the hippocampus in mnemonic and stress-related compartments was also evaluated. From all 113 patients, 18 % (n= 24) patients experienced emotional and psychological stress episodes directly before the TGA. In a cohort of 21 acute patients, TGA patients tend to cope with stress less efficiently and less constructively than controls. Patients who experienced a stress related precipitant event exhibited a higher level of anxiety in comparison to non-stress patients and controls. However, there was no difference between the general experience of stress and the number of stress inducing life events. The majority of patients (73%) did show typical MRI lesions in the CA1 region of the hippocampal cornu ammonis. There was no clear association between stressful events, distribution of hippocampal CA1 lesions and behavioral patterns during the TGA. Disadvantageous coping strategies and an elevated anxiety level may increase the susceptibility to psychological stress which may facilitate the pathophysiological cascade in TGA. The findings suggest a role of emotional stress factors in the manifestation of TGA in a subgroup of patients. Stress may be one trigger involved in the emergence of transient lesions in the hippocampal CA1 region, which are thought to be the structural and fun